Diabetes mellitus induced by immune checkpoint inhibitors. Issue 1 (24th July 2020) - Zheng, Zhenjiang; Liu, Ya; Yang, Jie; Tan, Chunlu; Zhou, Li; Wang, Xing; Xiao, Li; Zhang, Shu; Chen, Yonghua; Liu, Xubao
Abstract: Immune checkpoint inhibitors (ICIs) are widely used in oncology for their favourable antitumor efficacy. ICI therapy is associated with a unique toxicity profile known as immune‐related adverse events (irAEs). One such irAE is ICI‐related diabetes mellitus (DM), which is relatively uncommon but can become extremely severe, leading to irreversible impairment of β‐cells, and even lead to death if not promptly recognised and properly managed. The precise mechanisms of ICI‐related DM are not well understood. In this review, we summarise the clinical characteristics, pathophysiology, and management of this adverse effect caused by ICI therapy. Deeper investigation of ICI‐related DM may contribute to elucidate the molecular mechanisms of classical type 1 DM.